Rain, River, and Sea Water as Alternatives to Ground Water in the Fabric Coloration Industry - Hossain, Mohammad Mobarak; Das, Alok K.; Habiba, Ummay; Jamil, Siam Sarower; Kawser, Md Nakibul; Kundu, Chanchal Kumar; Islam, Tarikul; Farha, Waziha; Rahman, Mohammad Majibur (International Journal of Scientific Research and Management (IJSRM), 2025)
High consumption of water has resulted in a worldwide water disaster. The bulk of Bangladesh's textile industry is still not following the circular economy at the needed level. During the past two decades, as production and demand increased, so did the sector's usage of resources and energy to meet the objective of generating foreign currency, making it very difficult to achieve sustainability goals by 2030. This work investigates the possibilities of environmentally friendly alternative water sources in the coloration of cotton (cellulosic) and polyester (synthetic) fabrics. The standard recipe for three different shades % focused on their color fastness to rubbing, wash, and perspiration. Compared with groundwater or conventional water sources by the Bangladeshi industry, the result is amazing for sea, river, and rainwater. Though cotton fabrics show very poor color fastness properties 2-3 in most cases, polyester showed excellent results 4-5. It has also been discovered that in all circumstances, the same formula generates around 40-60% of the same qualities as traditional coloration with no additional adjustments to the recipe. This investigation determined that industrial dyeing processes may be realistically transferred into different water mediums to reduce groundwater use and achieve responsible consumption and sustainable development goals (SDG 12).